The Feminism Movement on the Hard Music Stage: An Analysis of the Unity/Safe Rooms of Indonesian NEGATIFA Band Songs - Maskuri, M. Ibnu Naufal; Daulay, Hamdan; Khadziq (Al Huwiyah: Journal of Woman and Children Studies, 2025)
This study analyzes the song Unity / Ruang Aman by the hardcore powerviolence band NEGATIFA as a medium of resistance against sexual violence in public spaces, particularly within Indonesia’s heavy music scene. The song was selected because it explicitly exposes incidents of harassment that occurred at concerts and asserts the urgency of safe spaces for women. A qualitative approach was applied through textual analysis of the lyrics, documentation of live performances, and theoretical framing using Alberto Melucci’s concept of collective identity and Stuart Hall’s theory of meaning negotiation. The findings reveal that the lyrics of Unity / Ruang Aman function as a form of cultural protest challenging patriarchal norms and false solidarity within the independent music community. Symbols such as “scene,” “stage dive,” and “bullshit unity” are transformed into discourses of resistance that reject victim blaming practices and demand collective accountability. Beyond criticism, the song promotes preventive mechanisms against sexual violence through on stage actions, direct calls to the audience, and the do it yourself networks characteristic of the hardcore subculture. This research demonstrates that heavy music can serve as an effective medium for education, gender equality campaigns, and social mobilization. The study contributes to music, gender, and social movement scholarship by showing how popular cultural practices can articulate demands for justice and construct a collective identity of resistance to sexual violence in public spaces.